Концептуальні засади розвитку та оцінки персоналу промислового підприємства на принципах соціальної відповідальності в умовах модернізації - Смирнова, І. І.; Сімаков, К. І.; Smyrnova, I. I.; Simakov, K. I. (Інститут економіки промисловості НАН України; Луганський національний університет імені Тараса Шевченка МОН України, 2020)
Метою статті є визначення основних засад поліпшення управління персоналом у сучасних умовах, застосування інноваційних підходів до формування ефективної системи оцінки та розвитку персоналу на принципах соціальної відповідальності для підвищення конкурентоспроможності підприємства.

The article explores the methodological foundations of the formation of an effective personnel assessment system based on social responsibility. It is determined that motivation plays a crucial role in the structure of a modern company, it permeates the organizational, economic, social and psychological spheres of interactions, thus, it is a circulatory system of the enterprise, which will enable all other bodies to function normally. It is determined that the main goal of enterprises in a competitive environment it becomes the development of strategies for the development of professional competence of enterprise personnel, where the main role is given to assessment, which is aimed at identifying the potential of each employee. The necessity of applying modern methods of personnel assessment based on the principles of social responsibility, as well as the importance of involving staff in regular assessment, including selfanalysis and selfdevelopment, was emphasized. The feasibility of developing an integrated methodological approach to the formation of an appropriate staff assessment based on the principles of social responsibility as an important element of effective management is sub-stantiated. A comprehensive assessment of the personnel of the enterprise on the principles of social responsibility to increase its competitiveness is proposed.
Conceptual Framework for the Development and Evaluation of Personnel of an Industrial Enterprise on the Principles of Social Re-sponsibility in Modernization
Keywords: Соціальна відповідальність; персонал; оцінка персоналу; методи оцінки персоналу; принципи оцінки персоналу; управління персоналом; конкуренто спроможність; мотивація; навчання та розвиток персоналу; social responsibility; personnel; personnel assessment; personnel assessment methods; personnel assessment principles; personnel management; competitiveness; motivation; staff training and development